2012
DOI: 10.1177/2156587212464652
|View full text |Cite
|
Sign up to set email alerts
|

Qigong Exercise in Patients With Fibromyalgia

Abstract: Fibromyalgia syndrome presents with widespread chronic pain and other symptoms. Approaches in alternative medicine offer promising results in managing fibromyalgia symptoms. Qigong exercise is a mind–body therapy originating in Chinese medicine that can benefit patients with fibromyalgia. We report 2 case studies of patients with fibromyalgia who completed a 6-week Qigong exercise program. In both cases, patients’ fibromyalgia symptoms improved after the Qigong exercise program. The patient in case 1 also expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…The identification of the different preoperative risk factors for PPOI (age, sex, cardiac comorbidities) in our study may provide surgeons with extra tools when assessing individuals undergoing colorectal surgery and help to identify high‐risk patients. These patients, in turn, may benefit from advance planning to minimize the development of PPOI (utilizing a laparoscopic approach, attempting to shorten the duration of surgery, avoiding the use of diverting stomas, among others) [79–82]. Other potential risk factors remain to be analyzed, including robotic versus laparoscopic surgery, analgesia technique, ERAS protocol, and patient‐related factors including hypothermia and visceral fat area.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of the different preoperative risk factors for PPOI (age, sex, cardiac comorbidities) in our study may provide surgeons with extra tools when assessing individuals undergoing colorectal surgery and help to identify high‐risk patients. These patients, in turn, may benefit from advance planning to minimize the development of PPOI (utilizing a laparoscopic approach, attempting to shorten the duration of surgery, avoiding the use of diverting stomas, among others) [79–82]. Other potential risk factors remain to be analyzed, including robotic versus laparoscopic surgery, analgesia technique, ERAS protocol, and patient‐related factors including hypothermia and visceral fat area.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicate that administration of TSFS results in remission of blood stasis. It is coincident with the pharmacological actions of Sanqi [20]. In comparison with administration TFFG alone, the AUC and C max of puerarin-7-O-glucuronide was increased (P < 0.05) after administration of TFFG combined with TSFS in blood stasis rats.…”
Section: Pharmacokinetic Parametersmentioning
confidence: 65%
“…Therefore, it is necessary to investigate the pharmacokinetics of the major constituents and metabolites in blood stasis rats after administration of Gegen in order to better understand its rational clinical application. Also, because of the common therapeutic effect of Gegen and Sanqi in promoting blood circulation and removing blood stasis [20], Gegen is often used in combination with Sanqi in clinical applications in order to obtain synergistic effects and reduce possible side effects [14]. Therefore, it is also essential to perform the pharmacokinetic studies to evaluate the compatibility of these combined treatments.…”
Section: Introductionmentioning
confidence: 99%
“…It also reduced chronic fatigue, gastrointestinal symptoms, cognitive confusion, 50 and sleep quality. 51 Finally, the combination of this therapy with meditation/relaxation and cognitive behavior therapies was analyzed by Creamer et al 52 They observed significant improvements in the reinterpretation of pain and rest, as well as a decrease in sensitivity of tender points four months after treatment. However, no improvement in emotional function was found, nor did the workdays lost due to illness be reduced.…”
Section: Discussionmentioning
confidence: 99%